The role of klotho in systemic sclerosis - R. Talotta; S. Bongiovanni; T. Letizia; F. Rigamonti; F. Atzeni; M. Benucci; T. Vago; P. Sarzi-Puttini (PAGEPress Publications, 2017)
The aim was to evaluate the role of klotho in the pathogenesis of systemic sclerosis (SSc), through the measurement of its serum concentration in SSc patients compared to healthy controls, and to assess the association with cutaneous and visceral involvement. Blood samples obtained from both SSc patients and healthy controls were analysed by an ELISA assay for the detection of human klotho. SSc patients were globally evaluated for disease activity and assessed through the modified Rodnan's Skin Score, Medsger's scale, pulmonary function tests, 2D-echocardiography, nailfold capillaroscopy and laboratory tests. Our cohort consisted of 69 SSc patients (61 females, mean age 64.5±12.5 years, median disease duration 9.0 (IQR 8) years) and 77 healthy controls (28 females, mean age 49.7±10.2 years). In the group of SSc patients, 19 (27.5%) suffered from a diffuse form of SSc. All patients were receiving IV prostanoids, and some of them were concomitantly treated with immunosuppressive drugs (prednisone, hydroxychloroquine, mofetil mycophenolate, methotrexate, cyclosporin A and azathioprine). The median serum concentration of klotho was significantly lower in patients compared to controls (0.23 ng/mL vs 0.60 ng/mL; p<0.001). However, Spearman's test showed no significant association between klotho serum levels and disease activity, concerning either clinical, laboratory or instrumental findings. Our data show a significant deficit of klotho in SSc patients although any significant association was detected between klotho serum concentration and the clinical, laboratory or instrumental features of the disease. However, due to the limits of the study, further investigations are required.